Regulation on Abortion Without a Medical Diagnosis in the Law of Crimes Performed By Medical Personnel - Boy Nurdin; Leti Ratna Kusumawati; Faisal Santiago (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Promiscuity among the public, teenagers, and the rise of prostitution today. This in turn encourages certain people who tend to have an abortion by carrying out illegal abortions as a solution to eliminating disgrace. The rise of the practice of abortion at this time seems to be a social phenomenon that is difficult to solve. From year to year, the number of people who practice abortion is increasing and of course, this is a reflection for all parties to be able to find the best solution in resolving abortion cases. Indonesia is regulated by Article 299, Article 346, Article 347, Article 348, and Article 349 of the Criminal Code. In addition to the Criminal Code, it has also been regulated in the Republic of Indonesia Law Number 36 of 2009 concerning Health which also regulates the crime of abortion contained in Article 75, Article 76, and Article 77. For perpetrators of illegal abortion, it is regulated in Article 194 RI Law Number 36 the Year 2009 concerning Health. Clearer terms and conditions regarding the implementation of permitted abortions are contained in Article 76 of Law Number 36 of 2009 concerning Health. The law (criminal) in viewing the practice of abortion can be seen from three articles, namely articles 346, 347, and 348 of the Criminal Code. If the practice of abortion is carried out by a doctor or other health worker, such as a midwife, the criminal liability is aggravated and can be increased by a third of the criminal threat contained in each proven article. And the right to carry out a search can be revoked, in casu SIP or STR, the doctor is the heart of the medical practice